From outside contributors to inside participants: Exploring how NGOs contribute to and participate in creating international law Examining the negotiations for the Ottawa convention banning landmines and the Rome Statute of the International Criminal Court - Hill, Gina E (University of Ottawa (Canada), 2008)
Within the current accepted paradigm of the international legal system, states are the only entities with the right to create international law. Recent experience however, shows that non-state entities, in particular non-governmental organizations, are increasingly becoming directly involved in the process of creating international law. This dissertation examines two cases -- the Ottawa Process to ban landmines, and the International Criminal Court negotiations -- to explore how NGOs contribute to international law creation, and whether they participate in the process of creating international law. In both cases NGOs engaged in a multitude of activities as they interacted with other entities involved in the negotiations. NGOs contributed to the process through: (a) agenda-setting; (b) creating conference agendas; (c) providing knowledge, expertise, and analysis; (d) negotiating with and between states; and (e) drafting instruments. In addition to these traditional activities, in these two cases NGOs also worked in coalition with each other, and with core-group and like-minded states to advance shared purposes. Multilateral negotiation theory and coalition dynamics offer a lens through which to understand how NGOs and states interacted with one-another in the process of creating international law. In working in alliances with similarly inclined states, NGOs contributed to three key aspects of coalition strength: (1) coalition size; (2) coalition diversity -- through naming and shaming, contributing different resources and bargaining skills, taking risks, and securing support from civil society to leverage governments; and (3) communication functions -- through intelligence networks, enrolment power, monitoring and analytical capacity, and institutionalized communications. NGOs worked alongside states, contributing to the effectiveness and strength of coalitions, and fulfilling the same roles as states, indeed, in some instances roles states could not fulfill on their own. By contributing to coalition strength and success, NGOs participated in the exercise of creating international law, even though they are not states. The result of this study is the recognition that two recent instances of international law creation fall outside the widely accepted understanding stating that only states create international law.
Keywords: Law.; Political Science, International Law and Relations.